2022
DOI: 10.14254/2071-789x.2022/15-3/10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the evolution of the educational attainment in economically active population in the regions of the Slovak Republic

Abstract: The economic development of countries is closely connected to human resources development. Education plays a pivotal role in the life of an individual and society as it provides chances for personal development and economic development of society. The Slovak Republic has been unable to cope with profound regional disparities in various areas for a long time. The existence of disparities is demonstrated by the evolution of educational attainment, which is integral to economic and regional development. The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In some papers, a bidirectional relationship was identified between schooling and employment: on the one hand, education ensures a drop in the unemployment rate [33], on the other hand, unemployment raises the demand for education which in turn determines people to invest in their own instruction [34]. Masarova et al's research findings revealed that the educational attainment of the active and employed population is increasing and that the educational level of the unemployed rises and falls irregularly depending on how the labor market evolves [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some papers, a bidirectional relationship was identified between schooling and employment: on the one hand, education ensures a drop in the unemployment rate [33], on the other hand, unemployment raises the demand for education which in turn determines people to invest in their own instruction [34]. Masarova et al's research findings revealed that the educational attainment of the active and employed population is increasing and that the educational level of the unemployed rises and falls irregularly depending on how the labor market evolves [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Karena tingkat pendidikan ini menggambarkan kecerdasan dan prestasi dari seseorang, yang nantinya akan membentuk kemampuan dari individu itu sendiri (Baskara et al, 2022). (Masárová et al, 2022) berpendapat bahwa tingkat pendidikan ataupun pelatihan yang tinggi dapat membuka dan memberi kesempatan yang lebih baik kepada seseorang, untuk mendapatkan pekerjaan, ataupun pengetahuan dan pemahaman yang baru. Pada dasarnya, tingkat pendidikan ini merupakan sarana untuk pengembangan Sumber Daya Manusia yang dilaksanakan terus-menerus dan bertahap untuk menjadikan SDM yang berkualitas (Aprilia et al, 2022).…”
Section: Tingkat Pendidikanunclassified
“…The higher education system has undergone several reforms in recent decades to ensure the quality of the offered study programmes as well as the quality of the universities themselves. Education has a significant impact on the development of a country, whether at the local or regional level (Masárová et al, 2022;Oliinyk et al, 2021). Of course, it is also important for the population, specifically for university graduates, who have a better chance of finding a job in the labour market than unqualified candidates.…”
Section: Introductionmentioning
confidence: 99%